The impact of thyroid-stimulating hormone levels in euthyroid women on intrauterine insemination outcome - Gorkem Tuncay; Abdullah Karaer; Ebru İnci Coşkun; Demet Baloğlu; Ayşe Nihan Tecellioğlu (BMC, 2018)
Abstract Background The aim of this study was to examine the effect of thyroid-stimulating hormone (TSH) levels on intrauterine insemination (IUI) outcomes among euthyroid women. Methods A retrospective cohort study was conducted. A total of 302 women who started their first IUI cycle in our fertility center were included in this study. The patients were categorized into two groups based on their preconception TSH values: 0.38-2.49 mIU/Land 2.50-4.99 mIU/L. The clinical pregnancy rate was the main outcome parameter. As secondary parameters, we evaluated the differences in spontaneous abortion rate, live-birth delivery rate, and perinatal outcomes according to the preconception TSH threshold (< 2.5 and < 5.00 mIU/L). Results There was no significant difference between the two groups with respect to clinical pregnancy, miscarriage, and live-birth rates with an odds ratio of 1.67 (95% CI: 0.79-3.53), 1.08 (95% CI: 0.09-13.1), and 1.79 (95% CI: 0.77-4.2), respectively. In addition, there were no significant differences in perinatal outcomes (gestation at delivery, birth weight, and neonatal intensive care unit-administration rate) between the two groups. Conclusions Our findings indicate that among euthyroid patients, preconception TSH values in the high-normal range (between 2.5 and 4.9 mIU/L) do not have a negative effect on IUI outcomes. Trial registration This study is retrospectively registered by Ethical Review Board at Inonu University in 19th December 2017; Ethics approval no is 2017-27-20.